2 Hypertension in Systemic Lupus Erythematosus Patients at Karawaci, Tangerang, Banten, Indonesia. (November 2017) - Kurniawan, Andree; Lugito, Nata Pratama Hadjo; Tjiang, Margaret Merlyn; Sumantri, Stevent; Soetjipto, Aurea S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease, usually affects women during their reproductive times. Risk for the development of cardiovascular disease is dramatically increased in SLE patients. Hypertension is a major risk factor for cardiovascular disease and the prevalent in women with SLE is still unknown especially in Asian patients. The aim of this study is to know the prevalence of hypertension in SLE patients and potential factors related. Method: This cross-sectional study evaluated SLE patients came to our Karawaci General hospital in period from 2013–2016. The diagnosis criteria of SLE was based on American Rheumatic Association (ARA) criteria. Hypertension diagnosed if blood pressure >140/90 in three measurements in the one-week period. Kidney ultrasound was done to know if the patients had chronic kidney disease (CKD) and CKD patients were excluded. Status of inflammation were evaluated using high-sensitive C-reactive protein (Hs-CRP). Result: One hundred twenty-two SLE patients were included to this study, 94.3% patients were female, and median of age was 31.5 (12–77) years old. Hypertension were found in 18(14.8%) patients. Nephritic syndrome was diagnosed in 67(54.9%) patients. Sixth nephritic patients had hypertension. Anti-Nuclear Antibody (ANA) was negative in 6(4.9%) patients. Fifteen (12.3%) patients had high Hs-CRP. High value of Hs-CRP did not correlate ( p < 0.286) with occurrence of hypertension but the odds ratio (OR) was 2.495 (0.349–17.81). Conclusion: Prevalence of hypertension in SLE patients was 14.8%. High Hs-CRP did not correlate to the occurrence of hypertension in SLE patients.